1994
DOI: 10.1021/bi00250a004
|View full text |Cite
|
Sign up to set email alerts
|

Orientation of Peptide Fragments from Sos Proteins Bound to the N-Terminal SH3 Domain of Grb2 Determined by NMR Spectroscopy

Abstract: NMR spectroscopy has been used to characterize the protein-protein interactions between the mouse Grb2 (mGrb2) N-terminal SH3 domain complexed with a 15-residue peptide (SPLLPKLPP-KTYKRE) corresponding to residues 1264-1278 of the mouse Sos-2 (mSos-2) protein. Intermolecular interactions between the peptide and 13C-15N-labeled SH3 domain were identified in half-reverse-filtered 2D and 3D NOESY experiments. Assignments for the protons involved in interactions between the peptide and the SH3 domain were confirme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
99
0

Year Published

1996
1996
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(108 citation statements)
references
References 34 publications
(51 reference statements)
9
99
0
Order By: Relevance
“…Despite the highly hydrophobic character of the ligand, this interaction is characterized by an extremely negative binding enthalpy (Ϫ92 kJ⅐mol Ϫ1 ) (12), which is notably bigger than the values reported for other SH3 complexes that typically range between Ϫ20 and Ϫ50 kJ⅐mol Ϫ1 (13)(14)(15)(16)(17). In previous work, we identified a set of fully buried water molecules at the binding interface that mediate the interactions between the peptide ligand and the SH3 domain and postulated that these water-mediated hydrogen bonds, which generate an extended and considerably more polar binding interface, are key for understanding the thermodynamic behavior of the system (12).…”
mentioning
confidence: 67%
See 1 more Smart Citation
“…Despite the highly hydrophobic character of the ligand, this interaction is characterized by an extremely negative binding enthalpy (Ϫ92 kJ⅐mol Ϫ1 ) (12), which is notably bigger than the values reported for other SH3 complexes that typically range between Ϫ20 and Ϫ50 kJ⅐mol Ϫ1 (13)(14)(15)(16)(17). In previous work, we identified a set of fully buried water molecules at the binding interface that mediate the interactions between the peptide ligand and the SH3 domain and postulated that these water-mediated hydrogen bonds, which generate an extended and considerably more polar binding interface, are key for understanding the thermodynamic behavior of the system (12).…”
mentioning
confidence: 67%
“…Nonetheless, all thermodynamic studies of SH3 ligand binding reported to date have surprisingly revealed an invariantly negative binding enthalpy that is partially compensated by unfavorable entropic contributions (12)(13)(14)(15)(16)(17). This thermodynamic behavior, which cannot be rationalized exclusively in terms of direct interactions between hydrophobic surfaces, reveals an underlying complexity in the recognition of proline-rich ligands by SH3 domains.…”
mentioning
confidence: 96%
“…The domain structure suggests that Dab2 is an adaptor protein involved in protein-protein interaction . The C-terminal proline-rich domain of Dab2-contains Grb2-binding motifs similar to that of the Ras guanine nucleotide exchanger Sos Lim et al, 1994;Wittekind et al, 1994). It has been shown previously that Dab2 binds Grb2 in vitro and in vivo, competing with Sos .…”
Section: Discussionmentioning
confidence: 99%
“…Sos1 binds Grb2 constitutively (Wittekind et al 1994;Houtman et al 2006). Following TCR ligation, Grb2 recruits Sos1 to the site of Ras localization at the membrane.…”
Section: Plc-g1 Binds Y132 Of Lat and Mediates Transcriptional Activamentioning
confidence: 99%